2012
DOI: 10.1371/journal.pone.0047845
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Niemann-Pick Disease, Type C1 Cerebellum Identifies Protein Biomarkers and Provides Pathological Insight

Abstract: Niemann-Pick disease, type C1 (NPC1) is a fatal, neurodegenerative disorder for which there is no definitive therapy. In NPC1, a pathological cascade including neuroinflammation, oxidative stress and neuronal apoptosis likely contribute to the clinical phenotype. While the genetic cause of NPC1 is known, we sought to gain a further understanding into the pathophysiology by identifying differentially expressed proteins in Npc1 mutant mouse cerebella. Using two-dimensional gel electrophoresis and mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 68 publications
5
79
0
Order By: Relevance
“…In contrast to CHO cells, the brain strongly relies on the oxidative metabolism of glucose and might be particularly sensitive to metabolic alterations caused by mitochondrial cholesterol accumulation. Moreover, decreased levels of non-phosphorylated, active PDH in Npc1 Ϫ/Ϫ murine cerebellum (7,36) and impaired mitochondrial ATP generation in the presence of pyruvate (7) indicate additional defects in pyruvate oxidation in NPC1-deficient brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to CHO cells, the brain strongly relies on the oxidative metabolism of glucose and might be particularly sensitive to metabolic alterations caused by mitochondrial cholesterol accumulation. Moreover, decreased levels of non-phosphorylated, active PDH in Npc1 Ϫ/Ϫ murine cerebellum (7,36) and impaired mitochondrial ATP generation in the presence of pyruvate (7) indicate additional defects in pyruvate oxidation in NPC1-deficient brain.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ/Ϫ cerebellum (7,36). If PDH inactivation contributed to the higher lactate production in NPC1-depleted CHO cells, we would expect a decrease in lactate production to the same levels in all cells by treatment with dichloroacetate, which indirectly activates PDH through inhibition of PDH kinase.…”
Section: The Increased Lactate Production By Npc1-depleted Cells Is Nmentioning
confidence: 99%
“…Two recent studies have reported that levels of mRNAs and proteins of several enzymes of energy metabolism are altered and that lactate levels are increased in NPC1-defi cient cerebella. Moreover, pyruvate oxidation is decreased and anaerobic glycolysis is increased during progression to the symptomatic stage of NPC disease ( 65,66 ). Thus, glucose metabolism appears to be affected at early stages of NPC disease.…”
Section: Clinical Manifestations Of Npc Deficiencymentioning
confidence: 99%
“…A fully automated 12-step MudPIT run was performed on each sample using a three mobile phase system consisting of buffer A (5% ACN; 0.1% FA), buffer B (80% ACN, 0.1% FA), and buffer C (500 mM ammonium acetate, 5% ACN, 0.1% FA). The first step was a 60 min reverse-phase run, whereas subsequent steps were of 120 min duration and included steps with 10,20,30,40,50,60,70,80,90, and 100% buffer C run for 4 min at the beginning of the gradient and a last step that includes salt bump of 90% buffer C with 10% buffer B for 4 min.…”
Section: Mass Spectrometry (Ms)mentioning
confidence: 99%